Does a Limited Defining Vocabulary Make Definitions Syntactically More Complex? - Kamiński, Mariusz Piotr (Studia Anglica Posnaniensia, 2020)
Definitions in learners’ dictionaries are usually written within a limited defining vocabulary (DV), that is, a set of lexical units specified prior to defining. Some researchers claim that this approach to vocabulary control may lead to definitions being syntactically complex, convoluted, and wordy. This paper aims to examine whether the introduction of a limited DV in OALD5 made its definitions more difficult to read for learners as compared to the definitions in OALD4, which were written with no explicit restrictions on the definition vocabulary. The study examines a selection of construction patterns that are potentially difficult for less advanced learners, using quantitative and qualitative methods. The examination shows that the introduction of the limited DV had no effect on most parameters studied. However, it led to significant increases in the length of definitions and the number of nominal constructions with a postmodifying past participle (e.g., performance given, spice ground, phrase used).